Quality certification and company performance – the newly developed country experience - Islam, Mohammad Mazharul; Habes, Essam; Karim, Azharul; Syed Agil, Syed Omar bin (Journal of Business Economics and Management, 2016)
This study investigates the impacts of ISO 9001:2008 certification on companies in Malaysia. Data were collected from CEOs and managers through a questionnaire survey. A multivariate analysis and SPSS macro were used as statistical techniques to assess the effects of ISO 9001 certification. Results of the study indicate that ISO 9001 certified companies were having significantly greater benefits and financial performance compared to non-certified companies. However, no significant direct relationship between ISO 9001 certification and company's financial performance was found. A further investigation revealed that financial performance is actually directly related to quality and local and international business performance, which are significantly influenced by ISO 9001 certification. Therefore quality and business performances are involved in the mediational process between the financial performance of companies and ISO 9001 certification. The novelty of this research lies in the establishment of, for the first time, high level statistical relationship between ISO 9001 certification, its mediating factors and financial performance of companies.First published online: 16 Dec 2015